INVENTORY OF POISINOUS MUSHROOMS AND CONSUMABLE MUSHROOMS IN THE BUKIT BARISAN TONGKOH FOREST PARK, NORTH SUMATERA - Napitupulu, David Sumanto; Seri Rayani Bangun (Jurnal EduHealth, 2022)
Macroscopic mushrooms can be divided into poisonous mushrooms and non-toxic mushrooms. In addition, there are also macroscopic mushrooms that can be consumed and cannot be consumed. The purpose of this study was to inventory the types of poisonous mushrooms and types of mushrooms that can be consumed in the Forest Park, Bukit Barisan Tongkoh, North Sumatera. The research was carried out from October 2021 to January 2022. Methods : the research method used was the cruise method. Sampling of mushrooms was carried out using the “purposive area sampling” method by looking at the characteristics of the mushrooms body as a description. Purposive area sampling method was used in species collection, and data were analyzed descriptively. As the results there were 8 genera of poisonous mushrooms found in that place, those were : Amanita sp, Collybia sp, Coprinus sp, Lactarius sp, Omphalotus sp, Panaeolus sp, Psathyrella sp and Scleroderma sp. In addition, we also found 7 genera of edible mushrooms. They were Agaricus sp, Cantharellus sp, Fammulina sp, Hygrocybe sp, Marasmius sp, Pluteus sp dan Volvariella sp. Each fungus is identified based on shape, size, texture, odor, substrate, spores, habitat and edibility.